Silicon- and Phosphate-Solubilizing Pseudomonas alkylphenolica PF9 Alleviate Low Phosphorus Availability Stress in Alfalfa (Medicago sativa L.) - El Moukhtari, Ahmed; Lamsaadi, Nadia; Farssi, Omar; Oubenali, Aziz; El Bzar, Ismail; Lahlimi Alami, Qamar; Triqui, Zine El Abidine; Lazali, Mohamed; Farissi, Mohamed (Frontiers in Agronomy, 2022)
Low phosphorus (P) availability is a major limiting factor facing current agriculture in several agricultural areas. Many P fertilizers are applied to enhance P availability, however the major part is likely to lose due to various processes related to P cycle. Silicon (Si) treatment and P-solubilizing bacteria inoculation have been emerged as a promising way to improve plant P nutrition. The current study aimed to investigate the synergistic effects of Si treatment and Pseudomonas alkylphenolica PF9 strain inoculation on plant growth, P nutrition, acid phosphatase (APase) activity, oxidative stress markers and antioxidant metabolism in the Moroccan alfalfa population Oued Lmalah (OL) under low-P availability. Results revealed a significant reduction in dry biomass, plant height, leaf number and area under low-P conditions. P-deficiency also altered P nutrition and chlorophyll (Chl) content. However, P-deficient alfalfa plants treated with Si or inoculated with PF9 strain displayed higher plant growth, Chl content, and remarkably the effect was much higher when Si was applied together with PF9 strain. Moreover, the simultaneous application of Si and PF9 strain to the P-deficient alfalfa plants improved APase activity and as a result P contents in both shoots and roots. Results also showed that the application of both Si and PF9 counteracted the low-P availability stress-induced oxidative damage by lowering the accumulation of reactive oxygen species, electrolyte leakage and lipid peroxidation. This seems to be related to the ability of both Si and PF9 strain to modulate both enzymatic and non-enzymatic antioxidant molecules including superoxyde dismutase activity, total polyphenols, flavonoids and proline contents. Our findings suggest that the combined application of Si and P. alkylphenolica PF9 strain could be a promising way for improving growth of alfalfa under low-P availability.